Facts with feelings – social workers' experiences of sharing information across team and agency borders to safeguard children. Issue 2 (3rd August 2016) - Lees, Amanda
Abstract: This paper reports findings from a psychosocially informed case study of information sharing across team and agency borders, carried out in three children and family social work teams within one local authority. The study investigated practitioners' understanding and experiences of information sharing, the tasks, processes and technologies involved, as well as perceived barriers and facilitators. It also considered how the emotional and social dynamics of working contexts could impinge upon information work. Practitioners described information tasks relating to collecting, interpreting, communicating and recording information, guided by the demands of rigid organizational protocols. Performance of these tasks was, however, infused by the emotional complexities of child protection work, presenting a number of challenges for practitioners seeking robust and reliable information in the midst of ambiguity, complexity and heightened emotions. For practitioners across all teams, information work, and information itself, was both cognitive and affective and often at odds with linear processes for its exchange across team boundaries, designed to filter out all but hard evidence. Increased recognition of the dual nature (facts and feelings) of information and information work, throughout the safeguarding process, has potential to enhance the generation of shared understandings and collaborative practice across team and agency borders.